A Combined User-order and Chunk-order Algorithm to Minimize The Average BER for Chunk Allocation in SC-FDMA Systems - Arfianto Fahmi; Rina Pudji Astuti; Linda Meylani; Muhamad Asvial; Dadang Gunawan (Universitas Ahmad Dahlan, 2016)
A Chunk by chunk-based allocation is an emerging subcarrier allocation in Single Carrier Frequency Division Multiple Access (SC-FDMA) due to its low complexity. In this paper, a combined user-order and chunk-order allocation for solving chunk allocation problem which minimizes the average BER of all users while improving the throughput in SC-FDMA uplink is proposed. The subcarrier grouping into a chunk of all users on both-order allocations are performed by averaging the BER of a contiguous subcarriers within a chunk. The sequence of allocation is according to the average of users’ BER on user-order allocation and the average of chunks’ BER on chunk-order allocation. The best allocation is determined by choosing one of both-order allocations which provides the smaller BER systems. The simulation results showed that the proposed algorithm can outperform the previous algorithms in term of average BER and throughput without increase the time complexity.